Traversing every edge in each direction once, but not at once: Cubic (polyhedral) graphs - Vladimir R. Rosenfeld (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2017)
A retracting-free bidirectional circuit in a graph G is a closed walk which traverses every edge exactly once in each direction and such that no edge is succeeded by the same edge in the opposite direction. Such a circuit revisits each vertex only in a number of steps. Studying the class Ω of all graphs admitting at least one retracting-free bidirectional circuit was proposed by Ore (1951) and is by now of practical use to nanotechnology. The latter needs in various molecular polyhedra that are constructed from a single chain molecule in the retracting-free way. Some earlier results for simple graphs, obtained by Thomassen and, then, by other authors, are specially refined by us for a cubic graph Q. Most of such refinements depend only on the number n of vertices of Q.